Characteristics of Arabian Sea mini warm pool during May 2003 - KUMAR, P. V. HAREESH; MADHUSOODANAN, P.; KUMAR, M. P. AJAI; RAO, A. RAGHUNADHA (MAUSAM, 2005)
Oceanographic surveys were carried out onboard INS Sagardhwani as a part of ARMEX in the deep and coastal regions of the eastern Arabian Sea during May 2003 to study the mini warm pool characteristics. The observational period was characterized by typical pre-monsoon conditions, as indicated by weak winds and clear skies. TMI SST data showed very good agreement with the ground truth observations (root mean square departure of ~0.2oC). Both the satellite imagery and ground truth showed surface temperature (SST) in excess of 31° C in the eastern Arabian Sea. This mini warm pool attained its maximum dimension ~8 days prior to the onset of summer monsoon over Kerala and the dissipated stated prior to the onset date. This information can be used as an index for the prediction of summer monsoon onset. Alternate bands of cyclonic and anti-cyclonic circulation pattern were evident both in the ground truth and satellite imagery. In the regions of SST more than 31° C, surface salinity was found to be less than 34.75 PSU and its depth extent was limited to thin surface layer resulting highly stratified layer. The low saline water present in this region was due to the northward / northwestward advection of low saline waters of equatorial Indian Ocean origin and the re-circulation of Bay of Bengal water mass trapped in the central Arabian Sea during winter by the eddy type of circulation.